2022
DOI: 10.23902/trkjnat.978842
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION OF GENES REGULATED IN RESPONSE TO Cu EXPOSURE IN Brassica nigra L.

Abstract: Copper (Cu) is one of the essential trace metals required for plant growth. High amount of Cu in the media inhibits plant growth and is toxic to the plants. Brassica nigra L., a Cu accumulator, can tolerate a high amount of Cu and have specific mechanisms to relocate Cu within the cell compartments and keep the toxic amount of Cu away from the cytoplasm. This study aimed to evaluate the Cu-induced gene expression pattern of B. nigra Diyarbakir ecotype subjected to low Cu treatment. The Arabidopsis ATH1 genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…However, that molecular response (NIP2.1, PIP1.1 and TIP1.1) was inversely dose-dependent. This is in agreement with previous research, in which low Cu treatment demonstrated a more positive impact on AQs expression than high Cu dosage (Landa et al, 2017;Merakli et al, 2021). Noteworthy, PIP1.1 and TIP1.1 expressions generally increase in plant tissues during intense growth as a means for effective water and solute circulation (Akdemir, 2021;Banerjee and Roychoudhury, 2020), which demonstrates a positive impact of Cu fertilization with low doses.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, that molecular response (NIP2.1, PIP1.1 and TIP1.1) was inversely dose-dependent. This is in agreement with previous research, in which low Cu treatment demonstrated a more positive impact on AQs expression than high Cu dosage (Landa et al, 2017;Merakli et al, 2021). Noteworthy, PIP1.1 and TIP1.1 expressions generally increase in plant tissues during intense growth as a means for effective water and solute circulation (Akdemir, 2021;Banerjee and Roychoudhury, 2020), which demonstrates a positive impact of Cu fertilization with low doses.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, as both Cu deficiency and excess impact the osmotic potential, significant changes in AQs expression were observed overtime (Kholodova et al, 2011;Merakli et al, 2021;Wintz et al, 2003). It is worth emphasizing that, only nano-Cu at 100 mg L -1 led to down-regulation of all tested AQs genes under a short-term exposure.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…GO-term analysis revealed that the N-treatment of E. gracilis and subsequent CdCl 2 exposure also enhanced expression of genes involved in “metal cluster binding” and “metal ion binding”. Through DGE we identified decreased expression of L-ascorbate peroxidase and increased expression of calmodulin, which have both been related to metal stress response by playing a key role in mitigating the oxidative stress response in plants 48 , 49 . Down regulation in E. gracilis suggests that the N-treatment suppressed this oxidative stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Through DGE we identi ed decreased expression of L-ascorbate peroxidase and increased expression of calmodulin which have both been related metal stress response. L-ascorbate peroxidase plays a key role in mitigating the oxidative stress response resulting from metal challenge in plants [34,35]. It's down regulation in E. gracilis suggests that N pre-treatment suppressed this oxidative stress response.…”
Section: Discussionmentioning
confidence: 99%